Long term effects of aromatase inhibitor treatment in patients with aromatase excess syndrome - Giannopoulou, Eleni Z.; Brandt, Stephanie; Zorn, Stefanie; Denzer, Christian; von Schnurbein, Julia; Fukami, Maki; Kaiser, Alexander; Schmidt, Martin; Wabitsch, Martin (Frontiers in Endocrinology, 2024)
Aromatase excess syndrome (AEXS) is a rare, autosomal dominant disorder, characterized by enhanced aromatization of androgens and estrogen excess. In males it is characterized by pre-/peripubertal gynecomastia, hypogonadotropic hypogonadism, advanced bone age and short adult height. Only a few female patients have been described so far. We report on a family with four members with AEXS and present the long-term effects of aromatase inhibitor use in three of them. Genetic analysis showed a monoallelic 0.3-Mb deletion in 15q21, involving parts of CYP19A1, GLDN and DMXL2 in all four patients with AEXS. The index patient (male, 8 years old) presented with gynecomastia and accelerated growth and bone age. With start of puberty, estradiol levels increased, while testosterone levels remained low.Gynecomastia progressed and a mastectomy was performed twice. Presuming AEXS, a therapy with letrozole was initiated at the age of 19 years. Low-dose letrozole treatment was associated with an increase in testicular volume, increase in virilization and improvement in physical strength and libido. His brother (age 3 years) presented with accelerated growth and bone age. Treatment with letrozole, which was started at the age of 7 years, resulted in achieving an adult height of 179 cm and prevented the appearance of gynecomastia. His sister (age 6 years), who presented with premature thelarche and accelerated growth and bone age, was treated with an estrogen receptor modulator and a GnRH analog followed by letrozole treatment. Menarche occurred at age 13.5 years and adult height was 158 cm. Their father had an early, accelerated growth with an adult height of 171 cm, a delayed puberty and no gynecomastia. In vitro studies provided evidence for involvement of aromatase induction in atypical cells and an increased range of potential mechanisms regulating aromatase activity due to the presence of the mutated allele. In conclusion, we observed a phenotypic variability within family members with AEXS carrying the same CYP19A1 microdeletion. When started early, treatment with letrozole was found to prevent the development of gynecomastia and increase adult height in one patient. In adult life, low-dose letrozole treatment resulted in improved physical strength and libido in the index patient.